The stem cell movement. - Smart, N; Riley, P (2008)
Stem or progenitor cell-based strategies to combat ischemic heart disease and myocardial infarction, whether autologous transplantation or stimulation of resident populations, not only require detailed insight into transdifferentiation potential and functional coupling, but the efficacy of this approach is underpinned by the need to induce appropriate migration and homing to the site of injury. This review focuses on existing insights into the trafficking of stem cells in the context of cardiac regenerative therapy, with particular focus on the wide variety of potential sources of cells, critical factors that may regulate their migration, and how extrapolating from embryonic stem/progenitor cell behavior during cardiogenesis may reveal pathways implicit in the adult heart postinjury.